The Effect of Environment Complexity and Resources on the Performance of SMEs Mediated By Business Strategy (Survey on Kasongan Pottery SMEs In Bantul Regency) - Wuryaningrum, Nuruita; Sabihaini, Sabihaini; Yudhiantoro, Danang (Universitas Dian Nuswantoro Semarang, 2022)
This study aims to analyze the effect of environmental complexity and resources on the performance of SMEs mediated by business strategy in Kasongan pottery SMEs. The population in this study were all SMEs pottery handicrafts in the Kasongan pottery center in Kasihan District, Bantul Regency, Yogyakarta. Total of 61 questionnaires have been returned and processed. The data analysis technique used was Partial Least Square (PLS) through SmartPLS 3.3.2 software. The research shows that environmental complexity has a positive and significant effect on performance of SMEs, resources have a positive and significant effect on performance of SMEs, environmental complexity has a positive and significant effect on business strategy, resources have a positive and significant effect on business strategy, and business strategy has a positive and significant effect on performance of SMEs. Also, it is found that environmental complexity has a positive and significant indirect effect on performance of SMEs through business strategy and resources have a positive and significant indirect effect on performance of SMEs mediated by business strategy. Keywords:Performance of SMEsEnvironment ComplexityResourcesBusiness strategy